Community dashboards to support data-informed decision-making in the HEALing communities study. (1st December 2020) - Wu, Elwin; Villani, Jennifer; Davis, Alissa; Fareed, Naleef; Harris, Daniel R.; Huerta, Timothy R.; LaRochelle, Marc R.; Miller, Cortney C.; Oga, Emmanuel A.
Highlights: The HEALing Communities Study relies on data-driven decision-making by communities. Community-tailored dashboards display opioid overdose death data and related measures. Dashboards are co-created by researchers and community stakeholders. Access to timely data can benefit other public health issues and health disparities. Abstract: Background: With opioid misuse, opioid use disorder (OUD), and opioid overdose deaths persisting at epidemic levels in the U.S., the largest implementation study in addiction research—the HEALing Communities Study (HCS)—is evaluating the impact of the Communities That Heal (CTH) intervention on reducing opioid overdose deaths in 67 disproportionately affected communities from four states (i.e., "sites"). Community-tailored dashboards are central to the CTH intervention's mandate to implement a community-engaged and data-driven process. These dashboards support a participating community's decision-making for selection and monitoring of evidence-based practices to reduce opioid overdose deaths. Methods/Design: A community-tailored dashboard is a web-based set of interactive data visualizations of community-specific metrics. Metrics include opioid overdose deaths and other OUD-related measures, as well as drivers of change of these outcomes in a community. Each community-tailored dashboard is a product of a co-creation process between HCS researchers and stakeholders from each community. The four research sites used a varied set of technical approaches and solutions to support the scientific design and CTH intervention implementation. Ongoing evaluation of the dashboards involves quantitative and qualitative data on key aspects posited to shape dashboard use combined with website analytics. Discussion: The HCS presents an opportunity to advance how community-tailored dashboards can foster community-driven solutions to address the opioid epidemic. Lessons learned can be applied to inform interventions for public health concerns and issues that have disproportionate impact across communities and populations (e.g., racial/ethnic and sexual/gender minorities and other marginalized individuals). Trial registration: ClinicalTrials.gov (NCT04111939)